Уникальные углекислые минеральные воды месторождения мухен (хабаровский край): состав и генезис - Харитонова Н. А.; Шварцев С. Л. Степан Львович; Петрова О. Е. Олеся Евгеньевна; Челноков Г. А. (2017, 2017)
Заглавие с экрана